Translating SOD1 Gene Silencing toward the Clinic: A Highly Efficacious, Off-Target-free, and Biomarker-Supported Strategy for fALS - Tommaso Iannitti; Joseph M. Scarrott; Shibi Likhite; Ian R.P. Coldicott; Katherine E. Lewis; Paul R. Heath; Adrian Higginbottom; Monika A. Myszczynska; Marta Milo; Guillaume M. Hautbergue; Kathrin Meyer; Brian K. Kaspar; et al. (Elsevier, 2018)
Of familial amyotrophic lateral sclerosis (fALS) cases, 20% are caused by mutations in the gene encoding human cytosolic Cu/Zn superoxide dismutase (hSOD1). Efficient translation of the therapeutic potential of RNAi for the treatment of SOD1-ALS patients requires the development of vectors that are free of significant off-target effects and with reliable biomarkers to discern sufficient target engagement and correct dosing. Using adeno-associated virus serotype 9 to deliver RNAi against hSOD1 in the SOD1G93A mouse model, we found that intrathecal injection of the therapeutic vector via the cisterna magna delayed onset of disease, decreased motor neuron death at end stage by up to 88%, and prolonged the median survival of SOD1G93A mice by up to 42%. To our knowledge, this is the first report to demonstrate no significant off-target effects linked to hSOD1 silencing, providing further confidence in the specificity of this approach. We also report the measurement of cerebrospinal fluid (CSF) hSOD1 protein levels as a biomarker of effective dosing and efficacy of hSOD1 knockdown. Together, these data provide further confidence in the safety of the clinical therapeutic vector. The CSF biomarker will be a useful measure of biological activity for translation into human clinical trials. : Development of off-target effect-free AAV9-shRNA-mediated SOD1 silencing in an ALS mouse model, with reliable biomarkers to discern sufficient target engagement and correct dosing. Keywords: ALS, AAV9, shRNA, SOD1, clinical vector, off-target effects, cisterna magna, neurodegeneration, motor neuron, biomarker